The proposal for the onerous right of building on the revision of Osasco´s master plan and its relationship with urban development - Paulino, Érica Aparecida de Jesus; Lima, Maytê Prado de (Technical and Scientific Journal Green Cities, 2021)
This article aims to analyze the proposal for the onerous right of building constant in the revision of Osasco’s Master Plan, which is in the process of being prepared, as an instrument for directing urban development. It has been made the analysis of the production of the real estate market with consumption of onerous right of building in the city from 2008 up to 2016, the existing legislation and the Master Plans’s proposal. It is noticed that the current legislation does not effectively bring about regulations regarding the direction of urban development in the city, a fact that tries to be corrected by the new proposal. Some principles based the proposal, such as the concentration of density together with the adequate structure of public transport, induction of housing uses in the popular market and of social interest in the regions best equipped with infrastructure and the supply of employment and non-residential use in the regions lacking in supply work, besides the protection of areas of environmental interest. This intentions, if materialized may give a new direction to urban development in the city.Keywords: Onerous right of building. Osasco. Urban development